Characteristic Analysis of Digital Emulsion Relief Valve Based on the Hydraulic Loading System - Lirong Wan; Hanzheng Dai; Qingliang Zeng; Zhenguo Lu; Zhiyuan Sun; Mingqian Tian; Yanjie Lu (Shock and Vibration)
In the hydraulic loading system, the performance of digital relief valve plays an important role in the dynamic response of load. However, the research on large-flow emulsion relief valve is still far from perfect. In this paper, digital relief valve is taken as the research object. Based on pilot-operated relief valve, a digital control scheme using a linear stepping motor is adopted to regulate the working pressure of relief valve. The structure of relief valve is analyzed and optimized from the aspects of dynamic and internal flow field characteristics to obtain a good working performance. To obtain its accurate working characteristic, the structural model and digital control system of relief valve are established by AMESim and Simulink, respectively, for electrohydraulic cosimulation. The results show that digital relief valve has a better characteristic of real-time dynamic pressure regulation. Therefore, the digital control system could improve the dynamic performance of relief valve, and the design of digital relief valve structure is reasonable and feasible. The simulation method employed in this paper provides a better theoretical basis and reference for the comprehensive research of digital large-flow emulsion relief valves based on the hydraulic loading system.